Case report: Long-term follow-up of two patients with LHON caused by DNAJC30:c.152G>A pathogenic variant-case series - Petrovic Pajic, Sanja; Jarc-Vidmar, Martina; Fakin, Ana; Sustar Habjan, Maja; Brecelj, Jelka; Volk, Marija; Maver, Ales; Peterlin, Borut; Hawlina, Marko (Frontiers in Neurology, 2022)
Background: We present a disease course and long-term follow-up in two patients who were phenotypically diagnosed as atypical Leber Hereditary Optic Neuropathy (LHON) 14 and 12 years ago whereby whole exome sequencing revealed recently described recessive DNAJC30 152 A>G (p.Tyr51Cys) homozygous pathogenic variant with significant spontaneous visual acuity recovery in one. Case presentation: Two presented unrelated males were followed for many years as atypical LHON with sequential VA loss. Patients had negative family history. At the presentation at ages 17 (Case 1) and 18 years(Case 2) both had reduced visual acuity (Snellen): (Case 1) RE:CF 3m, LE:0.6, (Case 2) RE:0.2, LE:0.15; and color vision (Ishihara): (Case 1) 1/15 and 13/15; (Case 2) 2/15 and 3/15. Both had hyperemic optic discs and central scotoma in visual fields. Electrophysiology in the acute phase showed reduced and delayed VEP P100 in both patients, with reduced N95 amplitude in Case 2, and initially normal in Case 1. Fluorescein angiography showed no early leakage with some late pooling at optic discs. Extensive clinical workout including brain MRI, Aq4, and anti-MOG antibodies was negative. Intravenous corticosteroids did not improve vision. Both experienced further deterioration several months after the onset accompanied by thinning of the peripapillary RNFL. Genetic testing for typical LHON pathogenic variants and whole mtDNA sequencing was negative. One year after the onset, modest VA improvement began in Case 2 and continued during the next 3 years. VA improved bilaterally to 0.7, color vision 15/15, and islands of vision appeared within the visual field scotoma. VEP P100 peak time shortened, and amplitude increased, despite further RNFL thinning on OCT. The patients’ visual function remained stable during the entire 12 year follow-up period. Case 1 experienced modest VA improvement to 0.1 with some improvement in the visual field seven years after the disease onset, remaining stable during the entire 14 year follow-up period. VEP P100 wave remained undetectable. Conclusions: Presented are two LHON AR cases with the same DNAJC30 pathogenic variant and different degrees of spontaneous visual recovery despite progressive RNFL thinning during a long-term follow-up. This mutation should be screened in every atypical LHON patient.